1990
DOI: 10.1038/346069a0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization and relaxation of arterial smooth muscle caused by nitric oxide derived from the endothelium

Abstract: Stimulation of the endothelial lining of arteries with acetylcholine results in the release of a diffusible substance that relaxes and hyperpolarizes the underlying smooth muscle. Nitric oxide (NO) has been a candidate for this substance, termed endothelium-derived relaxing factor. But there are several observations that argue against the involvement of NO in acetylcholine-induced hyperpolarization. First, exogenous NO has no effect on the membrane potential of canine mesenteric arteries. Second, although haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
168
2
5

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(188 citation statements)
references
References 22 publications
13
168
2
5
Order By: Relevance
“…However, the mechanism by which a high-salt diet induces BKCa channel involvement in EDHF-mediated response could not be discerned from this results. Although it has been reported that NO hyperpolarizes and relaxes arterial smooth muscle cells through the opening of potassium channels in certain vascular beds, 26 the activation of BKCa by NO is unlikely in this study as we and others have previously shown that hyperpolarization produced by ACh is not mediated by endogenous NO in rat mesenteric arteries. 11,27 Likewise, the activation of BKCa by H 2 O 2 , 28 a candidate for EDHF, 29 or by other reactive oxygen species is unlikely as we found no significant effect of catalase or apocynin on EDHF-like relaxation in mesenteric arteries of DS rats fed a high-salt diet.…”
Section: Upregulation Of Edhf In Salt-induced Hypertension K Goto Et Almentioning
confidence: 54%
“…However, the mechanism by which a high-salt diet induces BKCa channel involvement in EDHF-mediated response could not be discerned from this results. Although it has been reported that NO hyperpolarizes and relaxes arterial smooth muscle cells through the opening of potassium channels in certain vascular beds, 26 the activation of BKCa by NO is unlikely in this study as we and others have previously shown that hyperpolarization produced by ACh is not mediated by endogenous NO in rat mesenteric arteries. 11,27 Likewise, the activation of BKCa by H 2 O 2 , 28 a candidate for EDHF, 29 or by other reactive oxygen species is unlikely as we found no significant effect of catalase or apocynin on EDHF-like relaxation in mesenteric arteries of DS rats fed a high-salt diet.…”
Section: Upregulation Of Edhf In Salt-induced Hypertension K Goto Et Almentioning
confidence: 54%
“…NO activates directly K ϩ channels on smooth muscle cells (7). However, release of NO and activation of K ϩ channels may not be independent or mutually exclusive events because NO also relaxes veins by increasing cGMP levels (30), which in turn may activate Ca 2ϩ activated K ϩ channels (31,52). Cyclic nucleotide-gated channels, protein kinases, and/or phosphodiesterases (32) could be additional cGMP targets.…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments suggest that hyperpolarization of vascular smooth muscle is a mechanism shared by endotheliumdependent relaxing factors. NO itself hyperpolarizes vascular smooth muscle in many (Tare et al, 1990;Krippeit-Drews et al, 1992) but not all (Komori et al, 1988;Brayden, 1990) studies. In this paper we investigated which type of K + -channel was implicated in the relaxant e ect of L-citrulline on vascular smooth muscle and we found that K Ca -channels seem to be implicated in this e ect since apamin, a speci®c smallconductance K Ca -channel blocker, signi®cantly decreased the relaxation induced by L-citrulline, whereas glibenclamide, an ATP-dependent K + channel blocker, and charybdotoxin, a large-conductance K Ca -channel blocker, did not a ect the relaxant e ect of L-citrulline. Finally, L-citrulline, the byproduct in the synthesis of NO, may play a role in the control of vascular tone since its causes relaxation of vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%